A nanocrystal technology: to enhance solubility of poorly water soluble drugs - Mirza, R M; Ahirrao, S P; Kshirsagar, S. J. (Journal of Applied Pharmaceutical Research, 2017)
Most of the recently developed new chemical entities are poorly water soluble and they create major problems during formulation and development of new dosage form and due to poor solubility and poor bioavailability. The drugs belong to BCS class II and class IV has problem of solubility, to overcome the solubility problem nanotechnology is most useful technique. In this review article the main focus on Nanocrystals and various techniques used for preparation of Nanocrystals. Drug nanocrystals consists pure poorly water soluble drugs without any matrix material which means that it is carrier free drug delivery. Nanocrystals technologies have been introduced as advantageous, universal formulation approaches for the BCS class II and IV drugs. Nanocrystals, with greater surface to volume ratio, can effectively increase both the dissolution rate and saturation solubility of active ingredients The Nanocrystals is suitable drug delivery system for all commonly used routes of administration such as oral, IV, SC, and IM and topical application. Nanocrystals can also be incorporated into the tablets, capsules, fast-melts and lyophilized for sterile product applications. There are no of techniques which are used for production including precipitation, milling, high pressure homogenization and combination methods such as Nano-Edge, SmartCrystal and Precipitation-lyophilization-homogenization (PLH) technology.